Implementasi Kebijakan Pengelolaan Limbah Sampah Organik Di Tangerang Selatan - Fera, Yuliana; Nefianto, Tirton; Cholifihani, Muhammad; Hidayat, Yahya Rachmana; Wicaksana , Harits Hijrah (Jurnal Pendidikan Indonesia, 2025)
The purpose of discussing the implementation of organic waste management policies in South Tangerang is to see the implementation of waste disposal policies managed by the Environmental Service successfully become something that is beneficial to society and the state. The empirical condition of the waste problem is a social phenomenon that until now has not been able to be resolved completely by the Indonesian Government. The population is increasing day by day. The increasing population of people in urban areas makes settlements in each area become dense, so that the availability of land / settlements to fulfill people's residences is decreasing. Waste problems are still in the spotlight and almost all Tangerang Selatan cities experience problems in waste management. Especially in urban areas, managing urban waste can be said to be fairly difficult and has many challenges in its management. The larger the area of an urban area, the more waste will be generated so that management is more difficult. Waste management policies, especially food waste, can provide legal certainty in planning and utilization for the government, entrepreneurs, waste pickers, waste banks, communities, and the public. Policies in the form of programs to increase the role of the community by using the 3 R concept (Reduce, Reuse, and Recycle) are needed. Innovations continue to be developed where the main focus is to reduce waste and turn waste into renewable energy. Presidential Regulation of the Republic of Indonesia Number 35 of 2018 concerning the acceleration of the construction of waste processing installations into electrical energy based on environmentally friendly technology. a. that in order to increase the resilience of cities in maintaining public health and environmental quality, and to make waste a resource as mandated in Article 4 of Law Number 18 of 2008 concerning Waste Management, as well as to significantly reduce the volume of waste for the sake of cleanliness and beauty of the city, it is deemed necessary to accelerate the construction of Waste Processing installations into Electrical Energy Based on Environmentally Friendly Technology in certain provinces and districts / cities; b. that based on the considerations referred to in letter a, it is necessary to establish a presidential regulation concerning the Acceleration of the Construction of Waste Processing Installations into Electrical Energy Based on Environmentally Friendly technology.